2005
DOI: 10.1179/174329305x29500
|View full text |Cite
|
Sign up to set email alerts
|

Short fatigue crack growth behaviour of a ferritic steel weld metal

Abstract: The present study deals with the short fatigue crack growth behaviour of a ferritic steel (nuclear grade SA 333 Grade 6 steel) weld metal at two load ratios R of 0.1 and –1. Single edge notched weld joint specimens were tested at different stress levels. The acceleration and deceleration in short crack growth with increasing stress intensity factor range was explained in terms of microstructure of weld metal. Acicular ferrite and grain boundary ferrite acted as barriers to crack growth. Non-propagating cracks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…3. A few studies [75,76,78] highlighted the beneficial effect of acicular ferrite on fatigue resistance of the weld metal/HAZ, but these studies are based on either a narrow range of acicular ferrite fractions or limited quantitative analysis of the microstructures. There are, therefore, opportunities to quantitatively assess the influence of the evolution of the fraction of acicular ferrite on fatigue crack nucleation and propagation in the weld metal/HAZ.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…3. A few studies [75,76,78] highlighted the beneficial effect of acicular ferrite on fatigue resistance of the weld metal/HAZ, but these studies are based on either a narrow range of acicular ferrite fractions or limited quantitative analysis of the microstructures. There are, therefore, opportunities to quantitatively assess the influence of the evolution of the fraction of acicular ferrite on fatigue crack nucleation and propagation in the weld metal/HAZ.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of acicular ferrite in the microstructure of the weld metal has been shown to enhance fatigue crack growth resistance [75][76][77][78]. Similar to its effect on toughness, this enhancement is due to the interlocking nature of acicular ferrite and the relatively high density of high-angle boundaries that are present in the microstructure result [75,76,[79][80][81]. In particular, both Barbosa et al [76] and Lee et al [78] reported that weld metal had higher fatigue crack growth resistance than base metal in a steel weld joint, which was ascribed to the higher acicular ferrite fraction in the weld metal.…”
Section: Mechanical Performance Of Weld Metal/haz Containing Acicular...mentioning
confidence: 99%
See 2 more Smart Citations
“…Certainly, the fatigue crack initiation phase usually dominates fatigue lives, especially in the high cycle fatigue (HCF) regime [8], whereas fatigue cracks usually initiate in welded toe under elastic nominal stresses below the fatigue limit of the base metal. Approaches discussed 2 above are also unable to capture the intrinsic microstructural variability of fatigue failure due to the implicit assumption of isotropic homogeneous materials [9,10].…”
Section: Introductionmentioning
confidence: 99%